INKLUSI PADA SURAT KABAR ONLINE: ANALISIS WACANA KRITIS BERDASARKAN SUDUT PANDANG THEO VAN LEEUWEN - Winda - Azmi (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study aims to determine the contents of the theory of Leeuwen on online news coming from 5 sources, namely JavaPos.com, Okezone News, Rakyatku.com, Wahanariau.com, and Sindo News. The data in this study are phrases, clauses, and sentences related to inclusion in Leeuwen's theory with the theme of rape on online news. The source of this research data obtained from online news as much as 5 news. The data were analyzed by (1) identifying data according to Leeuwen's inclusion theory, (2) classifying the data based on the theory to be referenced, (3) analyzing the data by recording the phrase, the sense or phrases associated with Leeuwen inclusion theory, (4) interpreting data that has been analyzed with Leeuwen's inclusion theory, and (5) describing the description data by writing the report. The results of this study suggest that there is Leeuwen's inclusion theory on five online news with the theme of rape in the online news with the theme of rape as a whole the author does not side with the actor or writer and is also not aligned to the victim. Of the 5 online news analyzed, there is three news titled “Rape Teacher and Kill the Health Waiter, OPM Can not Sympathize the World "," Sadis ...! Beautiful Women Raped 8 Men, Then Killed, and Heads Round by Car, "and" Bumps Men Former Girlfriends After a Disappeared Invasion "that marginalized the victims and rape the rape. The author does not mention in detail who the perpetrators and victims. The author only uses the word youth or women in the news. Then, two other news entitled "Bejat! Rape and Kill His Own Sister with Sadis "and" Sadis, This Woman Raped 4 Men Until Killed "did not marginalize the perpetrators and the victims of rape. Here the authors side with the victim, visible from the punishment given to the expert.